2011
DOI: 10.1002/dvdy.22563
|View full text |Cite
|
Sign up to set email alerts
|

GMAP210 and IFT88 are present in the spermatid golgi apparatus and participate in the development of the acrosome–acroplaxome complex, head–tail coupling apparatus and tail

Abstract: We describe the localization of the golgin GMAP210 and the intraflagellar protein IFT88 in the Golgi of spermatids and the participation of these two proteins in the development of the acrosome-acroplaxome complex, the head-tail coupling apparatus (HTCA) and the spermatid tail. Immunocytochemical experiments show that GMAP210 predominates in the cis-Golgi whereas IFT88 prevails in the trans-Golgi network. Both proteins co-localize in proacrosomal vesicles, along acrosome membranes, the HTCA and the developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 42 publications
2
69
1
Order By: Relevance
“…In wild-type mice, vesicles positive for the IFT88-interacting protein GMAP210 (TRIP11) were seen first in cis-Golgi, and then they sequentially colocalized with IFT88 in proacrosomal vesicles, acrosome membranes, the head-tail coupling apparatus and developing tail. However, in Ift88 mutant mice, Golgi-derived GMAP210-positive vesicles did not reach the tail region, suggesting defective IMT (Kierszenbaum et al, 2011b).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In wild-type mice, vesicles positive for the IFT88-interacting protein GMAP210 (TRIP11) were seen first in cis-Golgi, and then they sequentially colocalized with IFT88 in proacrosomal vesicles, acrosome membranes, the head-tail coupling apparatus and developing tail. However, in Ift88 mutant mice, Golgi-derived GMAP210-positive vesicles did not reach the tail region, suggesting defective IMT (Kierszenbaum et al, 2011b).…”
Section: Introductionmentioning
confidence: 95%
“…Indeed, Ift88 mutant mice share similar defects with Kif3a knockout mice (Kierszenbaum et al, 2011b). In wild-type mice, vesicles positive for the IFT88-interacting protein GMAP210 (TRIP11) were seen first in cis-Golgi, and then they sequentially colocalized with IFT88 in proacrosomal vesicles, acrosome membranes, the head-tail coupling apparatus and developing tail.…”
Section: Introductionmentioning
confidence: 97%
“…It also provides a temporary niche for proteins in transit to the manchette, and places proteins close to a spermatid nuclear region where condensation and transcriptional silencing start. As the biogenesis of the acrosome-acroplaxome-manchette complex is in progress, microtubules and associated proteins with functional requirements in spermiogenesis-including keratin 5/Sak57, 3 GMAP210, 8 IFT88,8 Hook1, 9 Ran GTPase 10 and ODF2, 11 and components of the ubiquitin-proteasome system 12 -are transported to specific sites to transform a round spermatid into a self-propelling sperm.…”
Section: The Golgi the Origin Site Of Vesicular Cargos Transported Amentioning
confidence: 99%
“…15 More recently, it was shown that the golgin GMAP210 (for Golgi microtubule associated protein with a molecular mass of 210 kDa 16 ) resides in the cis-Golgi of spermatids and is involved in proacrosomal vesicle transport. 8 In somatic cells, GMAP210 is necessary for maintaining the integrity of the Golgi ribbon. 17,18 GMAP210 co-purifies with microtubules, 19,20 interacts with centrosomal γ-tubulin, 17 and when overexpressed perturbs the organization of the microtubule network.…”
Section: The Golgi the Origin Site Of Vesicular Cargos Transported Amentioning
confidence: 99%
See 1 more Smart Citation